Pemanfaatan Teknologi Penginderaan dalam Penentuan Pola Sebaran Biota Laut untuk Pencegahan Ilegal Fishing pada Laut Natuna Utara Guna Mendukung Sistem Pertahanan Negara - Debiyanti Debiyanti; Dadang Gunawan; Setyo Budiyanto (Departement of Mathematics Education, 2024)
Indonesia is a maritime country that has a variety of marine biota, especially the North Natuna Sea. This research focuses on the utilization of sensing technology to identify marine biota distribution patterns and prevent Illegal Fishing in the North Natuna Sea. In this context, maritime security becomes a critical aspect, involving not only protection from direct threats such as piracy or smuggling, but also issues such as Illegal Fishing and marine environmental pollution. The research uses the literature study method, collecting and analyzing data from various sources. The results show the importance of integrating advanced technologies such as satellites, radars and unmanned aircraft (UAVs) in maritime surveillance systems. International collaboration, especially with platforms such as the Indo-Pacific Regional Information Sharing (IORIS) and programs such as those run by the United States Coast Guard (USCG), has also proven important in strengthening Indonesia's maritime security capacity. This research emphasizes the importance of combining military and non-military defenses with remote sensing technologies to address threats and disruptions in Indonesia's maritime region.